2 Answers | Add Yours
So simplify 5/k + (k+3)/(k+5), we make the denominator the same for all the terms
=> [5(k + 5) + k(k+3)]/ k(k+5)
=> [5k + 25 + k^2 + 3k]/k(k+5)
=> (k^2 + 8k + 25)/k(k+5)
=> (k^2 + 8k + 25)/(k^2 + 5k)
The required result is (k^2 + 8k + 25)/(k^2 + 5k)
Given the expression:
E = 5/k + (k+3)/(k+5)
I am assuming that you need to write the expression as a single ratio.
Then, we need to determine the common denominator.
==> E = 5*(k+5) / k(k+5) + (k(k+3) / k(k+5)
Now we will open the brackets.
==> E = (5k+25)/(k^2+5k) + (k^2 + 3k)/ (k^2 + 5k)
==> E = (5k+25+ k^2 + 3k) / (k^2+5k)
Now we will combine like terms.
==> E = (k^2+8k+ 25) / (k^2 + 5k)
We’ve answered 317,420 questions. We can answer yours, too.Ask a question